2020
DOI: 10.1016/j.cmi.2020.08.003
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of a prediction model for severe respiratory failure in hospitalized patients with SARS-CoV-2 infection: a multicentre cohort study (PREDI-CO study)

Abstract: Objectives We aimed to develop and validate a risk score to predict severe respiratory failure (SRF) among patients hospitalized with coronavirus disease-2019 (COVID-19). Methods We performed a multicentre cohort study among hospitalized (>24 hours) patients diagnosed with COVID-19 from 22 February to 3 April 2020, at 11 Italian hospitals. Patients were divided into derivation and validation cohorts according to random sorting of hospitals. SRF was assessed from admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 22 publications
9
87
1
4
Order By: Relevance
“…In the larger New York cohort (13 442 patients with COVID-19 attending the emergency department), COPD was associated with an increased risk of hospitalisation (RR 1.77, 95% CI 1.67-1.87) [100], and a trend for increased mortality (RR 1.08, 95% CI 0.88-1.33). Similar findings were reported in an Italian cohort involving 1044 hospitalised patients; patients with COPD had significantly increased risk of severe respiratory failure (RR 1.17, 95% CI 1.09-1.27) [102]. In a Spanish longitudinal cohort, COPD was also associated with a 70% increase in the risk of death (RR 1.69, 95% CI 1.23-2.32) [111].…”
Section: Epidemiology and Clinical Outcomes Of Covid-19 In Copd Patientssupporting
confidence: 80%
See 2 more Smart Citations
“…In the larger New York cohort (13 442 patients with COVID-19 attending the emergency department), COPD was associated with an increased risk of hospitalisation (RR 1.77, 95% CI 1.67-1.87) [100], and a trend for increased mortality (RR 1.08, 95% CI 0.88-1.33). Similar findings were reported in an Italian cohort involving 1044 hospitalised patients; patients with COPD had significantly increased risk of severe respiratory failure (RR 1.17, 95% CI 1.09-1.27) [102]. In a Spanish longitudinal cohort, COPD was also associated with a 70% increase in the risk of death (RR 1.69, 95% CI 1.23-2.32) [111].…”
Section: Epidemiology and Clinical Outcomes Of Covid-19 In Copd Patientssupporting
confidence: 80%
“…Secondly, there is no clinical evidence that ICS are protective against COVID-19 or are associated with worse clinical outcomes [94]. Finally, whilst the available evidence from cohort studies does not demonstrate that COPD patients are more or less susceptible to acquiring infection with SARS-CoV-2, clinical outcomes including requirement for mechanical ventilation and mortality appear to be worse in COPD patients [102][103][104][105][106][107]111]. Support statement: This research was supported by the NIHR Manchester Biomedical Research Centre and the North West Lung Centre Charity, Manchester.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the combined effect of CKD and AKI as risk factors for mortality in COVID-19 has been poorly explored so far and our findings might provide interesting prognostic predictors to be further evaluated in this setting. Several mortality risk scores have been proposed to predict mortality in COVID-19 patients [12,33,34], most of which did not include an evaluation of kidney status. In our study cohort, patients with CKD complicated by AKI showed a significantly higher risk of score mortality by Zhao et al ≥ 2 as compared to patients with only acute or chronic kidney involvement or without kidney damage, respectively (74.7 vs 53.8 vs 67.0 vs 32.5, χ 2 131.7, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…During the manuscript writing, a scoring system of COVID-19 (CSS) was suggested that could help clinicians to identify high-risk patients with poor prognosis ( 13 ). Another promising predictive tool PREDI-CO score was suggested to be useful in resource allocation and treatment prioritization during the COVID-19 pandemic ( 14 ). We aimed to identify differences in patients' demographic, clinical, laboratory, and radiological findings between mild, severe, and critical cases of COVID-19 positive cases to develop and validate a diagnostic model predicting who will develop severe form and who will need critical care throughout the course of the disease.…”
Section: Introductionmentioning
confidence: 99%